2010
DOI: 10.17221/104/2009-pse
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal colonization and growth of Eremanthus incanus Less. in a highland field

Abstract: This paper focuses on Eremanthus incanus Less. (Asteraceae), a common species of highland regions in Brazil. The effect of arbuscular mycorrhizal (AM) inoculation on plant growth (height and diameter) was evaluated. Roots were examined from individuals randomly selected from undisturbed areas of highland vegetation and from an experimental restored site. Results showed that E. incanus presented high AM colonization both in restored and undisturbed sites. Moreover, AM colonization was significantly higher in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…This may owing to the ability of mycorrhiza to increase root surface area to uptake mineral contents and make phosphorus absorpable by plant roots. This result was in agreement with the finding of Pagano et al (2010) who reported that VAM colonization was significantly higher with the inoculated seedlings versus non-inoculated ones (control) and Tazisong et al (2015) who said that Phosphatases are responsible for the hydrolysis of a range of organic P compounds and provide mineral phosphate to the plant. Furthermore, Matias et al (2009) reported that the intensity of VAM colonization was also stimulated by plant growth.…”
Section: Discussionsupporting
confidence: 92%
“…This may owing to the ability of mycorrhiza to increase root surface area to uptake mineral contents and make phosphorus absorpable by plant roots. This result was in agreement with the finding of Pagano et al (2010) who reported that VAM colonization was significantly higher with the inoculated seedlings versus non-inoculated ones (control) and Tazisong et al (2015) who said that Phosphatases are responsible for the hydrolysis of a range of organic P compounds and provide mineral phosphate to the plant. Furthermore, Matias et al (2009) reported that the intensity of VAM colonization was also stimulated by plant growth.…”
Section: Discussionsupporting
confidence: 92%
“…Mycorrhizas also play an important role in biodiversity of plants and ecosystem functions ( Zhao et al, 2017 ; He et al, 2010 ), by influencing plant community diversity and composition ( van der Heijden et al, 1998 ; van der Heijden, 2004 ; Pagano, Cabello & Scotti, 2010 ). Therefore, AMF play a fundamental role in the origin, evolution, distribution, survival, growth, and development of plants and larger ecosystem scale processes ( Liu & Wang, 2003 ; Wang & Qiu, 2006 ; Mcguire et al, 2008 ; Hiiesalu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The last authors suggested that the occurrence of mycorrhiza and the density of AMF spores decreased along the succession, and it could be probably due to morphological root traits in fast-growing species that favored the contact with AMF propagules in the soil. Additionally, studies by Pagano et al (2008Pagano et al ( , 2010) also in semiarid fields of Minas Gerais State, showed higher mycorrhizal sporulation in disturbed sites.…”
Section: (G Potmentioning
confidence: 89%